Alliance for Innovation on Maternal Health: Consensus Bundle on Cardiac Conditions in Obstetric Care. Issue 2 (4th February 2023) - Hameed, Afshan B.; Haddock, Alison; Wolfe, Diana S.; Florio, Karen; Drummond, Nora; Allen, Christie; Taylor, Isabel; Kendig, Susan; Presumey-Leblanc, Garssandra; Greenwood, Emily
Abstract : In response to the high proportion of pregnancy-related deaths due to cardiac conditions, a multidisciplinary workgroup developed a patient safety bundle to provide evidence-based best practices to standardize and improve recognition and response to cardiac conditions and emergencies during pregnancy and postpartum. Abstract : Cardiac conditions are the leading cause of pregnancy-related deaths and disproportionately affect non-Hispanic Black people. Multidisciplinary maternal mortality review committees have found that most people who died from cardiac conditions during pregnancy or postpartum were not diagnosed with a cardiovascular disease before death and that more than 80% of all pregnancy-related deaths, regardless of cause, were preventable. In addition, other obstetric complications, such as preeclampsia and gestational diabetes, are associated with future cardiovascular disease risk. Those with cardiac risk factors and those with congenital and acquired heart disease require specialized care during pregnancy and postpartum to minimize risk of preventable morbidity and mortality. This bundle provides guidance for health care teams to develop coordinated, multidisciplinary care for pregnant and postpartum people with cardiac conditions and to respond to cardio–obstetric emergencies. This bundle is one of several core patient safety bundles developed by the Alliance for Innovation on Maternal Health that provide condition- or event-specific clinical practices for implementation in appropriate care settings. The Cardiac Conditions in Obstetric Care bundle is organized into five domains: 1) Readiness, 2) Recognition and Prevention, 3) Response, 4) Reporting and Systems Learning, and 5) Respectful Care . This bundle is the first by the Alliance to be developed with the fifth domain of Respectful Care . The Respectful Care domain provides essential best practices to support respectful, equitable, and supportive care to all patients. Further health equity considerations are integrated into elements in each domain.